Can digital skills raise occupational prestige among ethnic minorities?. Issue 2 (3rd April 2017) - Lissitsa, Sabina; Chachashvili-Bolotin, Svetlana; Bokek-Cohen, Ya'arit
Abstract : Using data from a large-scale Annual Social Survey of Israel's Central Bureau of Statistics, we investigate the correlation between digital skills and occupational prestige among veteran Jews and two minority groups, namely Arabs and immigrants to Israel from the Former Soviet Union (FSU). Our findings show that both minority groups have significant disadvantages in occupational prestige compared to veteran Jews. Although causation cannot be inferred because of the correlational design of our study, digital skills were found to contribute to occupational prestige among veteran Jews and FSU immigrants, beyond the classic socio-demographic factors. The occupational prestige gap between veteran Jews and FSU immigrants was eliminated after controlling for socio-demographic variables and before taking digital skills into consideration. The effect of digital skills on occupational prestige among Arabs was insignificant and after controlling for socio-demographic and digital skills, the gap in occupational prestige between veteran Jews and Arabs remained significant.